Pengaruh Penambahan Lemak Kakao (Theobroma cacao L.) dan Suhu Pemanasan terhadap Karakteristik Krim Ekstrak Kunyit (Curcuma domesticate Val.) - Cahyani, Nabila Ayu U.; Mulyani, Sri; Suwariani, Ni Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 1 (2020): MaretDO - 10.24843/JRMA.2020.v08.i01.p05, 2020)
Cream is a solid preparation in the form of an emulsion containing no less than 60% water. This study aims to determine the effect of cocoa butter substitution and process temperature on the characteristics of turmeric extract cream and determine the substitution of cocoa fat and process temperature to produce the best turmeric extract cream characteristics. This research uses factorial randomized block design. The first factor is the addition of cocoa butter which consists of 5 levels which is equal to 0g; 2.5g; 5g; 7.5g and 10g, and the second factor is the application of heating temperature which consists of two levels, 65 o C and 70 o C to produce 10 treatment combinations and grouped into two groups so that 20 experimental units are obtained. The parameters observed were homogeneity, pH, viscosity, dispersion, adhesion, separation ratio, total phenolic compounds, overall acceptance of the cream. the best treatment is determined by the effectiveness index. The results of the study stated that the treatment of cocoa butter substitution affected the pH, viscosity, spreadability, adhesion, separation ratio, total phenolic and acceptance test of cream preference and heating temperature had an effect on total phenolic cream. Process temperature has a significant effect on total phenolic cream. The treatment of cocoa butter and heating temperature have a very significant effect on the acceptance of the cream. The treatment of substitution of cocoa fat as much as 0% at a temperature of 70 o C heating process produces the best treatment with the following characteristics: 7800 cp viscosity, 6.3 cm diameter dispersion, separation ratio = 1, pH 6.40 and total phenolic 6.95 mg GAE / g. Keywords: cocoa butter, heating temperature, cream, turmeric